2021
DOI: 10.1007/s11195-021-09698-9
|View full text |Cite
|
Sign up to set email alerts
|

Dating with a Diagnosis: The Lived Experience of People with Multiple Sclerosis

Abstract: Multiple Sclerosis (MS) is a neurological condition which usually manifests between the ages of 20–40 years. This is a critical period for developing relationships, particularly romantic relationships. People with MS can experience sexual dysfunction, limb weakness, fatigue, pain, reduced mood and bladder/bowel dysfunction; potentially affecting their ability to participate in many meaningful activities, including those associated with romantic relationships, dating or engaging in sexual intercourse. Dating or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Studies examining romantic relationships have revealed that individuals with disabilities are often perceived as incompetent, helpless, and intellectually challenged (English et al, 2018; Shpigelman & Vorobioff, 2021; Tabassum et al, 2022). Furthermore, they may be regarded as “asexual” due to not fitting society’s ideal able-bodied image of beauty and desirability.…”
Section: Visible Versus Invisible Disabilitiesmentioning
confidence: 99%
“…Studies examining romantic relationships have revealed that individuals with disabilities are often perceived as incompetent, helpless, and intellectually challenged (English et al, 2018; Shpigelman & Vorobioff, 2021; Tabassum et al, 2022). Furthermore, they may be regarded as “asexual” due to not fitting society’s ideal able-bodied image of beauty and desirability.…”
Section: Visible Versus Invisible Disabilitiesmentioning
confidence: 99%